Peran Manajemen Sumber Daya Manusia dalam Organisasi - Irawan, Hendri (Jurusan PIPS FKIP UMMY Solok, 2021)
Writing aims to measure human resource management in organizations. The method uses the literature review method (library research). From the discussion it can be ignored that human resource management is human resources. Of the total resources available in the organization, human resources are very important and very determining. All potential possessed by human resources is very influential on the organization in achieving its goals.